Association of Common C-Reactive Protein (CRP) Gene Polymorphisms With Baseline Plasma CRP Levels and Fenofibrate Response - Shen, Jian (Diabetes Care, 2008)
OBJECTIVE: C-reactive protein (CRP) is an inflammatory marker that contributes to the prediction of cardiovascular disease. We investigated the influences of CRP polymorphisms on baseline CRP levels and fenofibrate-induced CRP changes in subjects with the metabolic syndrome. RESEARCH DESIGN AND METHODS: We examined the association of CRP single nucleotide polymorphisms (SNPs) (m772A>G, m301G>A >T, i178T>A, 3u1273C>T, and 3u2131C>T) with baseline plasma CRP levels among 1,123 white U.S. participants in the Genetics of Lipid Lowering Drugs and Diet Network (GOLDN) Study and the modulating effect of these SNPs on CRP response to a 3-week fenofibrate treatment among 290 participants with the metabolic syndrome. RESULTS: There were strong associations of m301G>A>T (rs3091244; P = 0.003), i178T>A (rs1417938; P = 0.001), 3u1273C>T (rs1130864; P = 0.001), and 3u2131C>T (rs1205; P < 0.001) with baseline CRP levels. Moreover, among subjects with the metabolic syndrome, fenofibrate induced the greatest reduction in CRP levels for TT subjects of the i178T>A compared with TA and AA subjects (−30 for TT, −19 for TA, and −11% for AA; P = 0.004). Similarly, for the m301G>A>T, major allele carriers displayed maximal reduction of CRP over noncarriers (−20 for GG, −15 for GA and GT, and −0.3% for TA and AA; P = 0.020). CONCLUSIONS: Our results demonstrate that common genetic variants within the CRP gene affect baseline CRP levels and further modulate CRP response in subjects with the metabolic syndrome treated with fenofibrate. This knowledge could contribute to a better prediction of therapeutic success.